Using aggregate flowability testing to predict lightweight self-consolidating concrete plastic properties. (September 2015) - Toutanji, H.; Goff, C.; Pierce, K.; Fares, H.
Abstract: This paper presents the results of an experimental study on the flow properties of lightweight self-consolidating concrete (LWSCC) which utilizes a new test relating aggregate flow to concrete flow. Three types of LWSCC were tested containing differing proportions of lightweight and normal weight, coarse and fine aggregates, as well as a normal weight self-consolidating concrete (NWSCC) as a control. The flow properties of the aggregate mixes used in the LWSCC and NWSCC specimens were tested using a V-funnel. The concrete flow properties were also tested for comparison, as were the compressive and tensile strengths of the various mixtures. A relationship between the aggregate frictional resistance and the traditional concrete flowability tests—i.e., slump flow, J-ring, and T500 —was demonstrated. Compressive strengths were greater in LWSCC mixes that contained smaller sized coarse and normal weight aggregates. Finally, a design procedure is introduced that utilizes the aggregate frictional resistance, paste flow properties, and aggregate void ratio to predict the plastic properties of the concrete.